'Doing' media studies: The media lab as entangled media praxis. (April 2019) - Thayne, Martyn; West, Andrew
Typically understood in relation to innovations in new media and modes of peer-production, the 'media lab' has emerged as a contemporary phenomenon encompassing a variety of 'maker-spaces', 'fablabs' and 'hackathons'. This article seeks to resituate the 'media lab' in the context of media research and education, drawing inspiration from the recent 'nonrepresentational' and 'nonhuman' turns in media and cultural theory that examine our entanglement with media on a social, cultural and biological level (Grusin, 2015b; Thrift, 2007; Vannini, 2015; Zylinska, 2012). This article contributes to such debates by presenting the lab as entangled media praxis as a set of 10 principles for teaching media as mediation : a reflexive form of 'doing' contemporary media studies that is primarily concerned with developing an embodied 'attunement' to the entangled relations of media lab participants. This framework calls for transdisciplinary modes of practice research and 'critical making', whereby students, artists, creative technologists and academics work collaboratively to address the affective and subjective conditions of contemporary digital culture. This article will explore these methods in relation to the concept of media entanglement, drawing out the underlying principles of the 'entangled media praxis' framework by examining two pilot media labs facilitated by the Arts Council England-funded project, 1215.today .